What are biblical values? : what the Bible says on key ethical issues - Collins, John J. (John Joseph), 1946- (Yale University Press, 2019)
An illuminating exploration of the Bible and many of our most contentious contemporary issues Many people today claim that their positions on various issues are grounded in biblical values, and they use scriptural passages to support their claims. But the Bible was written over the course of several hundred years and contains contradictory positions on many issues. The Bible seldom provides simple answers; it more often shows the complexity of moral problems. Can we really speak of "biblical values"? In this eye-opening book, one of the world's leading biblical scholars argues that when we read the Bible with care, we are often surprised by what we find. Examining what the Bible actually says on a number of key themes, John Collins covers a vast array of topics, including the right to life, gender, the role of women, the environment, slavery and liberation, violence and zeal, and social justice. With clarity and authority, he invites us to dramatically reimagine the basis for biblical ethics in the world today